Ultrasonic Sensor based Automated Floor Cleaner - B.Anishfathima, Dr.C.Thirumarai Selvi, R.Swathika & S.Ramkumar, M.V. Shreenidhi3 (International Journal of Advanced Science and Technology, 2020)
The aim of this idea proposal is to design in automated floor cleaner using ultrasonic sensor. This is patterned based on pulse width modulation (PWM) Cruise controller. The perspective conceives depend on pic microcontroller along with the hardware and software prospectus are unveiled. The management framework moves the machine either in the front or back likewise including the task actions with the help of direct current motor consequently, the performance of an automated floor cleaner is favorably actualized.